The triterpenoid and steroid from the fruiting body of Ganoderma applanatum (Pers.) Pat. In Viet Nam - Hoang Van Trung; Nguyen Tan Thanh; Nguyen Ngoc Tuan; Doan Manh Dung; Tran Dinh Thang (Vietnam Journal of Science and Technology, 2018)
Five compounds, ergosterol (1), 5α,8α-epidioxy-22E-ergosta-6,22-dien-3β-ol (2); ergosta-7,22-dien-3β-ol (3); lanosta-7,9(11),24-triene-3,26-diol (4) and 3β-hydroxy-5α-lanosta-7,9,24(E)-trien-26-oic acid (5) were isolated from fruiting body of Ganoderma applanatum (Pers.) Pat. (Ganodermataceae). The structures of the isolated compounds were established by spectroscopic methods (UV, IR, MS, 1H-NMR, 13C-NMR, DEPT, COSY, HSQC and HMBC). These compounds were isolated from the Vietnamese fungi for the first time. Moreover, the lanosta-7,9(11),24-triene-3,26-diol is the first compound was found in the fungi.